إشكالية المنهج الأصولي في الفكر الاجتهادي المعاصر Problem of Jurisprudential Method in the Contemporary Ijtihadi Thought - (Halima Boukerroucha), حليمة بوكروشة (Journal of Islam in Asia (E-ISSN 2289-8077), 2012)
إن الدعوات المعاصرة إلى فتح باب الاجتهاد، وإعماله في جميع مجالات الحياة اقتضت كما يرى كثير من المفكرين المسلمين تجديد النظر في منظومة علم أصول الفقه بما يضمن استيعاب المستجدات، وتحقيق الاستجابة المطلوبة للتحديات التشريعية، والفكرية التي تواجه المشروع الإسلامي، غير أن المتأمل في الأطروحات النقدية للمنهجية الأصولية يجدها تفتقر إلى إشكالية واضحة، ومنضبطة، الأمر الذي أفرز توجهات في إطار الحركة النقدية، لكل منها تصورها الخاصللإشكالية، ولمنهج معالجتها.وهذا البحث محاولة لتسليط الضوء على هذه التوجهات، وبحث مقارباتها بحثا نقديا يخرج إشكالية المنهج الأصولي من دائرة الجدل النظري إلى دائرة الإنتاج المعرفي. الكلمات المفتاحية: المنهج الأصولي، الفكر الاجتهادي، مقاصد الشريعة، الأدلة الشرعية، المنهج التجريبي. ******************************** The contemporary calls to open the door of ijtihad and its realization in all areas of life require, as many Muslim intellectuals view, to revise the principles of Islamic jurisprudence so as to ensure the inclusion of new developments and achieve the desired response to the legislative and intellectual challenges faced by the Islamic project. However, a thoughtful person finds the criticism of jurisprudential method problematic and lacking in clarity and organization, which has resulted in the development of different trends in the critical circle, with each of them having its own vision of the problem. This research is an attempt to shed light on these trends, analyze critically their methodological problem, and suggest methodological remedy that can replace theoretical debate with result-oriented experimental endeavor. Key words: jurisprudential method, Ijtihadi Thought, Intentions of Share‘ah, Religious Evidences, Experimental Method.